2009
DOI: 10.2174/156720209788185605
|View full text |Cite
|
Sign up to set email alerts
|

Blood Brain Barrier Compromise with Endothelial Inflammation may Lead to Autoimmune Loss of Myelin during Multiple Sclerosis

Abstract: Multiple sclerosis is an autoimmune disease characterized by multifocal areas of inflammation and demyelination within the central nervous system. The mechanism that triggers the disease remains elusive. However, recent findings may indicate that multiple sclerosis, at its source, could be a hemodynamic disorder. It has been found that multiple sclerosis patients exhibit significant stenoses in extracranial veins draining the central nervous system (in azygous and internal jugular veins), which are associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 64 publications
0
31
0
Order By: Relevance
“…Key to this barrier are endothelial cells of the CNS blood vessels forming tight junctions, facilitating exclusion of constituents of the systemic circulation from entry into the CNS. It is noteworthy that only recently has it been hypothesized that endothelial cells of the blood-brain barrier might contribute to immune signaling within the CNS (Quan et al, 2003;Simka, 2009). After a tissue insult and the ensuing release of peripheral or central immune signals, the tight junctions become leaky, exposing the CNS to peripheral immune signals (Stamatovic et al, 2003;Song and Pachter, 2004;Bennett et al, 2010).…”
Section: A What Do Immunocompetent Cells Contribute Tomentioning
confidence: 99%
“…Key to this barrier are endothelial cells of the CNS blood vessels forming tight junctions, facilitating exclusion of constituents of the systemic circulation from entry into the CNS. It is noteworthy that only recently has it been hypothesized that endothelial cells of the blood-brain barrier might contribute to immune signaling within the CNS (Quan et al, 2003;Simka, 2009). After a tissue insult and the ensuing release of peripheral or central immune signals, the tight junctions become leaky, exposing the CNS to peripheral immune signals (Stamatovic et al, 2003;Song and Pachter, 2004;Bennett et al, 2010).…”
Section: A What Do Immunocompetent Cells Contribute Tomentioning
confidence: 99%
“…Inflammatory cell adhesion molecules, such as the intercellular adhesion molecule-1, vascular cell adhesion molecule-1, and selectins, are potential target molecules for the treatment of brain ischemia and MS. This is because the adhesion of activated leukocytes to BCECs induces secondary neuronal injury after reperfusion 4,5 and immune-mediated demyelination in MS. 6,7 In Alzheimer's disease (AD), inhibition of the receptor for advanced glycation end products (RAGE) can be expected to alleviate AD pathology, because RAGE expressed in BCECs mediates an influx transport of the neurotoxic amyloid-β peptide (Aβ) from the blood into the brain. 8,9 RNA interference is a powerful tool to achieve post-transcriptional gene silencing.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated an association of CCSVI with MS [1,6,7,16], and it was hypothesised that impaired cerebral venous drainage may lead to local venous hypertension and dysfunction of the bloodbrain barrier, which in turn may evoke autoimmune reaction and neurodegeneration [17]. Still, an association of CCSVI with MS was not confirmed by many authors, probably not only because of the different diagnostic protocols used, but primarily due to much a more complex relationship between CCSVI and MS than was initially believed [18].…”
Section: Discussionmentioning
confidence: 99%